Long-term safety and limited organ damage in patients with systemic lupus erythematosus treated with belimumab: a Phase III study extension. (13th July 2019) - van Vollenhoven, Ronald F; Navarra, Sandra V; Levy, Roger A; Thomas, Mathew; Heath, Amy; Lustine, Todd; Adamkovic, Anthony; Fettiplace, James; Wang, Mei-Lun; Ji, Beulah; Roth, David
Abstract: Objective: This extension study of the Phase III, randomized, placebo-controlled Belimumab International SLE Study (BLISS)-52 and BLISS-76 studies allowed non-US patients with SLE to continue belimumab treatment, in order to evaluate its long-term safety and tolerability including organ damage accrual. Methods: In this multicentre, long-term extension study (GlaxoSmithKline Study BEL112234) patients received i.v. belimumab every 4 weeks plus standard therapy. Adverse events (AEs) were assessed monthly and safety-associated laboratory parameters were assessed at regular intervals. Organ damage (SLICC/ACR Damage Index) was assessed every 48 weeks. The study continued until belimumab was commercially available, with a subsequent 8-week follow-up period. Results: A total of 738 patients entered the extension study and 735/738 (99.6%) received one or more doses of belimumab. Annual incidence of AEs, including serious and severe AEs, remained stable or declined over time. Sixty-nine (9.4%) patients experienced an AE resulting in discontinuation of belimumab or withdrawal from the study. Eleven deaths occurred (and two during post-treatment follow-up), including one (cardiogenic shock) considered possibly related to belimumab. Laboratory parameters generally remained stable. The mean (s .d .) SLICC/ACR Damage Index score was 0.6 (1.02) at baseline (prior to the first dose of belimumab) and remained stable. At study year 8, 57/65 (87.7%) patients had no change in SLICC/ACR Damage Index score from baseline, indicating low organ damage accrual. Conclusion: Belimumab displayed a stable safety profile with no new safety signals. There was minimal organ damage progression over 8 years. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT00424476 (BLISS-52), NCT00410384 (BLISS-76), NCT00732940 (BEL112232), NCT00712933 (BEL112234).